2012
DOI: 10.1615/jwomenminorscieneng.2013004491
|View full text |Cite
|
Sign up to set email alerts
|

Portraits of Science Self-Efficacy: Four Undergraduate Women in a Summer Research Experience

Abstract: maximize the number of students involved in research. Our Behavioral Research Advancements in Neuroscience (BRAIN) research program tests the hypothesis that a team-based collaborative-learning model not only provides research opportunities for more students, but also produces outcomes at least

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although comprehensive and especially rich when considered together with our preliminary quantitative report ( Goode et al ., 2012 ) and our qualitative case study ( Britner et al ., 2012 ), this report has some limitations. Perhaps of greatest concern is the observation that increased scientific research self-efficacy during the program did not predict retention in a research career path.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although comprehensive and especially rich when considered together with our preliminary quantitative report ( Goode et al ., 2012 ) and our qualitative case study ( Britner et al ., 2012 ), this report has some limitations. Perhaps of greatest concern is the observation that increased scientific research self-efficacy during the program did not predict retention in a research career path.…”
Section: Discussionmentioning
confidence: 95%
“…Bandura (1977) described four sources of self-efficacy: mastery experiences, vicarious experiences, social persuasion, and physiological/emotional states. On the basis of an in-depth qualitative analysis of four participants, students in our program attributed gains in self-efficacy to mastery experiences, such as engagement in tasks, interpretation of results, and developing beliefs in their capacity to perform tasks in accordance with the results, for example: “[Having been] through the process once … next time I’ll know what I’m doing and what to look for in a project and how to design one” ( Britner et al ., 2012, p. 283 ). Although this analysis was based on pre/postprogram interviews, without a midprogram interview to provide higher temporal resolution, it is possible that influential mastery experiences occurred earlier in the summer for the CLM participants, perhaps in the form of acquiring independent research skills in the first few weeks of the crayfish lab and/or generating hypotheses and designing experiments by the midprogram time point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research self-efficacy, therefore, is a student’s self-perception of their ability to perform research-related tasks and activities [ 60 ]. Research on science self-efficacy indicates it is a predictor of a students’ persistence in science-related fields [ 61 ]. Research self-efficacy and research skills were found to predict students’ aspirations for research careers, and the effects of research skills are partially mediated through self-efficacy beliefs [ 62 ].…”
Section: Introductionmentioning
confidence: 99%